DEVOTION TO COMMUNITIES â€œPOSYANDUâ€ GROUP OF PREGNANT MOTHER THROUGH INTRODUCTION TO HAZARD SIGNS IN PREGNANCY SUB-DISTRICT MEDAN SUNGGAL - Girsang, Bina Melvia; Karo, Evi Indriani; Sari, Farida Linda (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Recognition of pregnancy danger plays an important role in preventing and reducing maternal mortality. Pregnant women can identify the danger signs of pregnancy. Therefore, the danger signs during pregnancy need to be known by pregnant women, especially those that threaten the health of the mother and the fetus who are pregnant. The minimum needs to be known by pregnant women in the community to recognize pregnancy danger signs, namely bleeding out of birth canal, excessive nausea, preeclampsia and eclampsia , premature rupture of membranes, and fetal movements that are not felt. Medan Sunggal Health Center is one of the village areas assisted by the USU Nursing Faculty. Based on the results of previous studies of pregnant women, it was found that there were still many pregnant women who did not know about the signs and dangers during pregnancy. The main cause is the limited knowledge of mothers about the signs and dangers of pregnancy and the mother's skills to overcome the lack of information about the signs and dangers of pregnancy. Posyandu cadres who have played an active role have been felt to be weak in providing education about information on signs and harms of pregnancy. Posyandu cadres have the potential for their role as agents of change. Therefore to overcome the problem of lack of information about the signs and dangers of pregnancy, it is necessary to improve the method of delivering information on signs and dangers of pregnancy, by involving several parties who can later collaborate in dealing with information problems for pregnant women, involving KIA officers from Sunggal Health Center, cadres , and invite pregnant women.